Meningkatkan Kesehatan Ibu Pascapersalinan melalui Model Promosi M-Health Interaktif - Wulandari, Respati (Jurnal Abdimas Jatibara, 2022)
Introduction: The postpartum period is a risky period. Maternal mortality in Semarang City was ranked in the top 5 in 2015-2018. Almost 75% of maternal deaths in the city of Semarang occur during the puerperium.Objectives:  to increase the participant’s understanding so that they can apply an interactive online health promotion model for postpartum care at the Bandarharjo Public Health Center, SemarangMethods: The approach used in this activity is to explain the model, how to apply the model, and the benefits obtained for midwives and couples of pregnant women and husbands. This activity also shows flyers and promotional videos explaining how to assist pregnant women and husbands during the model intervention.Results: A total of 9 participants consisting of the Head of the Puskesmas, coordinating midwives, midwives, health promotion workers, and nurses, participated in this activity. Analysis of the questionnaire responses showed that the model was attractive, could help the midwife's work, needed, useful, practical, innovative, easy to use, informative, and trustworthy. The overall assessment of the model by the participants was acceptable. Input from one of the participants was to provide a promotional video link to make it easier for members to search again and propose to design a stunting prevention promotion model.Conclusions:  The use of an interactive online health promotion model for postpartum care can be accepted by health workers to help promote health for pregnant women and husbands.